1999
DOI: 10.1063/1.123247
|View full text |Cite
|
Sign up to set email alerts
|

Structure and magnetic properties of Gd3(Fe1−xCox)25Cr4 compounds

Abstract: The structural and magnetic properties of Gd3(Fe1−xCox)25Cr4 compounds with x=0–0.6 have been investigated. The structures of all the compounds investigated are found to possess monoclinic symmetry and belong to the A2/m space group. Substitution of Co for Fe leads to a clear contraction of the unit-cell volume. The Curie temperature increases from 492 K for x=0 to 762 K for x=0.6. The composition dependence of the saturation magnetization at 5 K reaches a maximum around x=0.3. It is noteworthy that substituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…In order to investigate the room temperature magnetocrystalline anisotropy of the compounds, the XRD patterns of [11,12], where the anisotropy at room temperature is dependent on the content of Co and has an easy-axis-type anisotropy for x 10. It is well known that in the R-T compounds there exist three exchange interactions: the R-R interactions between the R magnetic moments within the R sublattice, the T-T exchange interactions between the T magnetic moments within the T sublattice and the R-T interactions between the R moments and T moments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to investigate the room temperature magnetocrystalline anisotropy of the compounds, the XRD patterns of [11,12], where the anisotropy at room temperature is dependent on the content of Co and has an easy-axis-type anisotropy for x 10. It is well known that in the R-T compounds there exist three exchange interactions: the R-R interactions between the R magnetic moments within the R sublattice, the T-T exchange interactions between the T magnetic moments within the T sublattice and the R-T interactions between the R moments and T moments.…”
Section: Resultsmentioning
confidence: 99%
“…Yang et al [10] have synthesized Sm 3 (Fe,Ti) 29 N y compounds that exhibit outstanding intrinsic permanent magnetic properties. Subsequently, Yang et al [11] and Wang et al [12] have synthesized Gd 3 Fe 29−x−y Co x Cr y compounds with the substitution of Co for Fe and found that Gd 3 (Fe 1−x Co x ) 25 Cr 4 compounds show a room temperature uniaxial magnetocrystalline anisotropy for x 0.4, which is important for application as permanent materials. These results indicated a prospective application of the noninterstitial R 3 M 29−x T x compounds as permanent magnetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Nd 3 (Fe 1 − x Co x ) 27.7 Ti 1.3 compounds it has been found that the canted anisotropy (x = 0) turns gradually to uniaxial for x > 0.1, towards the [4 0 −2] direction which corresponds to the c-axis of the 1:12 phase and lies in the 1:5 basal plane [4]. Yang et al [5] and Wang et al [6] observed that for the case of Gd 3 (Fe 1 − x Co x ) 25 Cr 4 compounds the anisotropy is planar with the EMD also lying near to the [4 0 −2] direction. For x > 0.3 the Gd containing compounds also change the anisotropy to uniaxial, but here the EMD lies perpendicular to the basal plane towards the [2 0 4] direction.…”
Section: Introductionmentioning
confidence: 97%
“…In order to improve the understanding of the behavior of Co and Fe in R 3 (Fe, TM) 29 substituted alloys, several groups have studied the replacement of Fe by Co in this system synthesized with various rare earths [1][2][3][4][5][6][7][8][9]. It has been shown that the Curie temperature, the saturation magnetization, and the magnetocrystalline anisotropy of these compounds are strongly affected by the Co content.…”
Section: Introductionmentioning
confidence: 98%
“…y = 1.5) a disordered variant of the hexagonal Th 2 Ni 17 -type structure is formed [12]. Yang et al [13] have investigated the structure and magnetic properties of the Gd 3 (Fe 1−x Co x ) 25 Cr 4 compounds with x ranging from 0 to 0.6 and found that when x > 0.4 the compounds show room temperature uniaxial anisotropy. Uniaxial anisotropy has been also observed in the case of Nd when 0.1 < x < 0.4 [7], and Sm [5,11].…”
Section: Introductionmentioning
confidence: 98%